Adaptive Peacebuilding A New Approach to Sustaining Peace in the 21st Century - de Coning, Cedric; Saraiva, Rui; Muto, Ako (Twenty-first Century Perspectives on War, Peace, and Human Conflict, 2023)
This open access book responds to the urgent need to improve how we prevent and resolve conflict. It introduces Adaptive Peacebuilding through evidence-based research from eight case studies across Africa, Asia, the Middle East, and Latin America. It also considers how China and Japan view and practice peacebuilding. The book focuses on how peacebuilders design, implement and evaluate programs to sustain peace, how interactions between external and local actors have facilitated or hindered peacemaking, and how adaptation to complexity and uncertainty occurred in each case study.